Conjunctival Goblet Cell Responses to TLR5 Engagement Promote Activation of Local Antigen-Presenting Cells - Logeswaran, Abiramy; Contreras-Ruiz, Laura; Masli, Sharmila (Frontiers in Immunology, 2021)
Conjunctival epithelium forms a barrier between the ocular surface microbial flora and the ocular mucosa. In addition to secreting gel-forming mucins, goblet cells, located in the conjunctival epithelium, help maintain local immune homeostasis by secreting active TGFβ2 and promoting tolerogenic phenotype of dendritic cells in the vicinity. Although dendritic cell subsets, characteristic of mucosal tissues, are found in the conjunctiva, previous studies provided limited information about their location within the tissue. In this study, we examine immunostained conjunctiva explants to determine the location of CD11c-positive dendritic cells in the context of MUC5AC-positive goblet cells. Considering that conjunctival goblet cells are responsive to signaling induced by pathogen recognition receptors, we also assess if their responses to microbial product, flagellin, can contribute to the disruption of ocular mucosal homeostasis that promotes activation of dendritic cells and results in chronic ocular surface inflammation. We find that dendritic cells in the conjunctiva with an increased microbial colonization are located adjacent to goblet cells. While their cell bodies in the stromal layer are immediately below the epithelial layer, several extensions of dendritic cells are projected across the epithelium towards the ocular surface. Such trans-epithelial dendrites are not detectable in healthy ocular mucosa. In response to topically applied flagellin, increased proportion of CD11c-positive cells in the conjunctiva strongly express MHC class II relative to the untreated conjunctiva. This change is accompanied by reduced immunoreactivity to TGFβ-activating Thrombospondin-1 in the conjunctival epithelium. These findings are supported by in vitro observations in primary cultures of goblet cells that respond to the TLR5 stimulation with an increased expression of IL-6 and reduced level of active TGFβ. The observed changes in the conjunctiva after flagellin application correspond with the development of clinical signs of chronic ocular mucosal inflammation including corneal epitheliopathy. Collectively, these findings demonstrate the ability of ocular mucosal dendritic cells to extend trans-epithelial dendrites in response to increased microbial colonization at the ocular surface. Moreover, this study provides key insight into how goblet cell responses to microbial stimuli may contribute to the disruption of ocular mucosal homeostasis and chronic ocular mucosal inflammation.